The effect of transdermal scopolamine for the prevention of postoperative nausea and vomiting - Antor, María A.; Uribe, Alberto A.; Erminy-Falcon, Natali; Werner, Joseph G.; Candiotti, Keith A.; Pergolizzi, Joseph V.; Bergese, Sergio D. (Frontiers in Pharmacology, 2014)
Postoperative nausea and vomiting is one of the most common and undesirable complaints recorded in as many as 70%-80% of high-risk surgical patients. The current prophylactic therapy recommendations for PONV management stated in the Society of Ambulatory Anesthesia guidelines should start with monotherapy and patients at moderate to high risk, a combination of antiemetic medication should be considered. Consequently, if rescue medication is required, the antiemetic drug chosen should be from a different therapeutic class and administration mode than the drug used for prophylaxis. The guidelines restrict the use of dexamethasone, transdermal scopolamine, aprepitant, and palonosetron as rescue medication 6 hours after surgery. In an effort to find a safer and reliable therapy for postoperative nausea and vomiting, new drugs with antiemetic properties and minimal side effects are needed, and scopolamine may be considered an effective alternative. Scopolamine is a belladonna alkaloid, α-(hydroxymethyl) benzene acetic acid 9-methyl-3-oxa-9-azatricyclo non-7-yl ester, acting as a nonselective muscarinic antagonist and producing both peripheral antimuscarinic and central sedative, antiemetic, and amnestic effects. The empirical formula is C17H21NO4 and its structural formula is a tertiary amine L-(2)-scopolamine (tropic acid ester with scopine; MW = 303.4). Scopolamine became the first drug commercially available as a transdermal therapeutic system used for extended continuous drug delivery during 72 hours. Clinical trials with transdermal scopolamine have consistently demonstrated its safety and efficacy in postoperative nausea and vomiting. Thus, scopolamine is a promising candidate for the management of postoperative nausea and vomiting in adults as a first line monotherapy or in combination with other drugs. In addition, transdermal scopolamine might be helpful in preventing postoperative discharge nausea and vomiting owing to its long-lasting clinical effects.